(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2017)
District office is one of the government agencies. This office certainly produces documents in every administrative process and policy. The document management provides a good solution for each document in order to be accessed and used by users. The improper document management causes difficulty to find the needed documents. Moreover, the document is very difficult to access because it is only kept by certain people for various reasons. Besides, the document is also public rights that should be accessed by many people. An Act number14 in 2008 on Public Information Disclosure indicates that the document is a certain entity to reduce a public dispute so that it is mandatory matter that must be done. Under this condition, it is expected that the document must be stored in the websitebased application to allow all parties to easily access the document stored.